Lands’ lead bread “, development and decline of the hacienda of Cuisillos (Tzintzun, Revista de Estudios Históricos, 2016)
This paper is a brief summary of the historical trajectory of the Haciendaof Cuisillos, Jalisco. The interest in such property lies, firstly, to contributeto historiographical knowledge about the central area of the state ofJalisco, and secondly, to make relevant the changes and continuities experiencedin a farm such as Cuisillos along its nearly 400 years, similar toother large properties in western Mexico. The work begins with an overviewof how the property was consolidated, emphasizing its importantrole, especially for the supply of Guadalajara, capital of the vast territorythen known as Nueva Galicia. Then continues with an analysis of theproperty after different owners own the place throughout the colonialera and during the independence period. Finally, we conducted a breakdownof how Cuisillos lost their land to peasants living in villages andpeons of the haciendas. Haciendas that had monopolised the land in theValley of Tala.
Keywords: Hacienda Cuisillos; Tala Valley; New Galicia; large estates